Candidates for the 5α condensed state in 20Ne - Adachi, S.; Fujikawa, Y.; Kawabata, T.; Akimune, H.; Doi, T.; Furuno, T.; Harada, T.; Inaba, K.; Ishida, S.; Itoh, M.; Iwamoto, C.; Kobayashi, N.; et al. (Physics letters. B, 2021)
We conducted the coincidence measurement of α particles inelastically scattered from 20Ne at 0° and decay charged particles in order to search for the alpha-particle condensed state. We compared the measured excitation-energy spectrum and decay branching ratio with the statistical-decay-model calculations, and found that the newly observed states at Ex=23.6, 21.8, and 21.2 MeV in 20Ne are strongly coupled to a candidate for the 4α condensed state in 16O. This result presents the first strong evidence that these states are the candidates for the 5α condensed state.